MITOLOGI SEBAGAI LANDASAN PENGUAT PRAKTEK RITUAL HINDU - I Gusti Ketut Widana; I Ketut Winantra; Dewa Kadek Sudyana (UNHI PRESS, 2022)
One of the reinforcing foundations in Hindu ritual practice is matters related to mythology (myth). The basis of this mythology is related to something 'occult' and even 'mystical' which is packaged in the form of a story or story, complete with all sanctions, precisely the risks that can occur and be experienced if you do not carry out as mandated. This mythological foundation then makes Hindus in carrying out their yadnya ritual obligations so obedient, submissive and sometimes even shrouded in fear. Fear not to do what is told in the myth. Because in the myth also equipped with various kinds of risks in the form of threats and even punishments that can occur, befall or be experienced by the people. This article will examine why mythology is the basis for strengthening every ritual practice of Hindus. ABSTRAK Salah satu landasan penguat dalam praktik ritual Hindu adalah hal-hal yang berhubungan dengan mitologi (mitos). Landasan mitologi ini berhubungan dengan sesuatu yang bersifat ‘gaib’ bahkan ‘mistis yang dikemas dalam bentuk cerita atau kisah, lengkap dengan segala sanksi, tepatnya risiko yang bisa terjadi dan dialami jika tidak melaksanakan sebagaimana sudah diamanatkan. Landasan mitologi ini kemudian menjadikan umat Hindu dalam melaksanakan kewajiban ritual yadnya begitu taat, tunduk bahkan adakalanya diselimuti rasa takut. Takut untuk tidak melaksanakan apa yang dicerita-kisahkan dalam mitos. Sebab di dalam mitos tersebut juga dilengkapi beraneka rupa risiko berupa ancaman bahkan hukuman yang bisa terjadi, menimpa atau dialami umat. Artikel ini hendak mengkaji mengapa mitologi menjadi landasan penguat dalam setiap praktik ritual umat Hindu.